EDUKASI HIPERTENSI DAN DIET DASH MENGGUNAKAN MEDIA VIDEO ANIMASI PADA PASIEN HIPERTENSI - Cahyaningrum, Aladhiana; Laraeni, Yuli; Ananda Liza Aryansyah Putri; Gumilang Pratiwi, Intan (Poltekkes Kemenkes Mataram, 2025)
Hypertension is known as the silent killer because it typically doesn't cause symptoms or complaints, so many sufferers are unaware of it. Central Lombok Regency has the second-highest number of hypertension cases in West Nusa Tenggara Province, with 58,666 cases, consisting of 27,980 men and 30,686 women. Most people with hypertension are unable to control their condition, likely due to varying knowledge and perceptions about managing their condition. One health program that can be used to change attitudes among people with hypertension is to provide nutritional information or education about the DASH diet, which is essential for blood pressure control. The purpose of this Community Service Program (PKM) is to increase the knowledge of hypertensive patients in an effort to improve their health status so that blood pressure remains under control and thus can prevent or inhibit complications of other diseases. The PkM activity was carried out through direct counseling for outpatients at the Praya Health Center using video media, and blood pressure measurements and measuring pre-post-test knowledge. The results of this PkM activity were increased patient knowledge and an average patient blood pressure of 145.5 mmHg for systolic blood pressure and 85,3 mmHg for diastolic blood pressure